2018
DOI: 10.1177/0198742917747595
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Risk for Emotional and Behavioral Disorders in Late Elementary School: A Comparison of Two Targeted Interventions

Abstract: Early indicators of risk correspond with behavioral disorders in childhood and beyond (Webster-Stratton & Reid, 2003). One early indicator of future negative short-and long-term outcomes is early school failure, which predicts compounded mental health issues, problem behavior and peer problems, exclusionary discipline (suspension, expulsion), grade retention, substance abuse, arrest and adjudication, and school dropout (Crews et al., 2007; Nelson, Stage, Trout, Duppong-Hurley, & Epstein, 2008). Longterm negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Results indicated that schools must initially establish strong Tier 1 systems and practices that promote universal mental wellness and prevent mental health concerns to efficiently and effectively affect students needing supplemental supports due to internalizing behaviors. Building on the need to identify students not responding well to Tier 1 supports, McDaniel et al (2018) examined the the effects of check-in/ check-out and Coping Power interventions as Tier 2 interventions and how to best match student deficits to appropriate evidence-based interventions. Whereas the targeted interventions produced positive behavioral change, results showed that without an intervention, students who were nominated and rated by their teachers as exhibiting high levels of problem behaviors did not decrease their level of risk without intervention.…”
Section: Purpose Of This Issue and Overview Of Articlesmentioning
confidence: 99%
“…Results indicated that schools must initially establish strong Tier 1 systems and practices that promote universal mental wellness and prevent mental health concerns to efficiently and effectively affect students needing supplemental supports due to internalizing behaviors. Building on the need to identify students not responding well to Tier 1 supports, McDaniel et al (2018) examined the the effects of check-in/ check-out and Coping Power interventions as Tier 2 interventions and how to best match student deficits to appropriate evidence-based interventions. Whereas the targeted interventions produced positive behavioral change, results showed that without an intervention, students who were nominated and rated by their teachers as exhibiting high levels of problem behaviors did not decrease their level of risk without intervention.…”
Section: Purpose Of This Issue and Overview Of Articlesmentioning
confidence: 99%
“…Coping Power intervention effects on multiple indices of problem behavior have also been found with youth diagnosed with disruptive behavior disorders [ 25 , 26 , 27 , 28 , 29 ], with students with behavior problems in dissemination and implementation studies in schools and community settings [ 30 , 31 , 32 , 33 , 34 , 35 ], and with children in other cultural environments [ 36 , 37 , 38 ]. When Coping Power has been implemented as a treatment for children with disruptive behavior disorders, it may also have a subsequent preventive effect for adolescent substance abuse and delinquent behavior.…”
Section: Introductionmentioning
confidence: 99%